Intermittent MHD structures and classical discontinuities - Greco, Andres Francisco (2008)
We examine statistics of rapid spatial variations of the magnetic field in simulations of magnetohydrodynamic (MHD) turbulence, by analyzing intermittency properties. and by using classical methods for identifying discontinuities. The methods identify similar structures, and give very similar event distribution functions. When the results are scaled to the correlation length, the average waiting times agree with typically reported waiting times between solar wind discontinuities. Thus discontinuities may be related to flux tube boundaries and intermittent structures that appear spontaneously in MHD turbulence. Copyright 2008 by the American Geophysical Union.